2018
DOI: 10.1039/c8ra04958k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient (Cu1−xAgx)2ZnSn(S,Se)4 solar cells on flexible Mo foils

Abstract: Cation substitution plays a crucial role in improving the efficiency of Cu 2 ZnSn(S,Se) 4 (CZTSSe) solar cells. In this work, we report a significant efficiency enhancement of flexible CZTSSe solar cells on Mo foils by partial substitution of Cu + with Ag + . It is found that the band gap (E g ) of (Cu 1Àx Ag x ) 2 ZnSn(S,Se) 4 (CAZTSSe) thin films can be adjusted by doping with Ag with x from 0 to 6%, and the minimum E g is achieved with x ¼ 5%. We also found that Ag doping can obviously increase the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
2
20
2
Order By: Relevance
“…This representation has been chosen to evidence that the incorporation of Ag is not beneficial for kesterite devices despite numerous attempts to optimize the performances of CAZTSe-based solar cells. At first sight, this result is in contradiction with numerous previous studies [6][7][8][9][10][11][12][13] in which an optimum is found at low (but not null) ACA ratios. All the literature data concerning Ag alloying for kesterite solar cells have been shown in Figure 6b along with the state-of-the-art PCE for sulfur, selenium, and sulfoselenium Ag-free absorbers.…”
Section: Homogeneous Alloyingcontrasting
confidence: 99%
See 2 more Smart Citations
“…This representation has been chosen to evidence that the incorporation of Ag is not beneficial for kesterite devices despite numerous attempts to optimize the performances of CAZTSe-based solar cells. At first sight, this result is in contradiction with numerous previous studies [6][7][8][9][10][11][12][13] in which an optimum is found at low (but not null) ACA ratios. All the literature data concerning Ag alloying for kesterite solar cells have been shown in Figure 6b along with the state-of-the-art PCE for sulfur, selenium, and sulfoselenium Ag-free absorbers.…”
Section: Homogeneous Alloyingcontrasting
confidence: 99%
“…b) Literature review of the maximum PCE for CAZTS(S)(e) as a function of the ACA ratio. [6][7][8][9][10][11][12][13] Stars represent the state-of-the-art efficiency for CZTS, CZTSSe, and CZTSe solar cells respectively. [17][18][19] The dashed line is a guide for the eye.…”
Section: Graded Alloyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical calculations demonstrated that due to a substantially larger ionic radius of Ag + (1.14 Å) in comparison with Cu + (0.74 Å) or Zn 2+ (0.74 Å), the formation energy of the AgZn defect (at 0.2 eV above the valence band edge) is much larger than that of the CuZn defect (0.12 eV). Many reports indeed showed an improved lattice (cationic) order in (Cu1-xAgx)2ZnSn(S,Se)4 (CAZTS) or Ag2ZnSn(S,Se)4 (AZTS), as well as a concomitant increase of the photovoltaic device efficiency [5,7,8], although also adverse effects of the substitution were reported [9]. It should be noted that embedding a high Ag concentration into the (intrinsically p-type) CZTS alters the conductivity to n-type [8].…”
Section: Introductionmentioning
confidence: 99%
“…The latter problem is generally believed to originate from band tails caused by Cu-Zn antisite defects [4]. Partial substitution of Cu for Ag is supposed to be a promising approach to reduce the antisite defect density and thus the band tailing [5,6]. Theoretical calculations demonstrated that due to a substantially larger ionic radius of Ag + (1.14 Å) in comparison with Cu + (0.74 Å) or Zn 2+ (0.74 Å), the formation energy of the AgZn defect (at 0.2 eV above the valence band edge) is much larger than that of the CuZn defect (0.12 eV).…”
Section: Introductionmentioning
confidence: 99%